Psychology intersecting what? - Parker, Ian (PINS-Psychology in Society, 2025)
PINS has been an important reference point for radicals in psychology in the UK, those of us who now sometimes go under the heading “critical psychology”, and when we have tried to connect our critique of psychology with practical action the struggle in South Africa was always on our minds. You were there for us, for example, in academic conferences where we attempted to inject something of the real world into abstract debates about “social constructionism”, and you were there when we took some first steps to mobilise researchers alongside those who use psychological services in the founding of the organisation “Psychology Politics Resistance”. Sometimes the events in South Africa functioned as inspiration and sometimes as a warning; of how political revolution feeds into the composition of psychology as a discipline, and of how a change in constitutional dispensation can reproduce old structures and effectively absorb and neutralise complaint.